2021
DOI: 10.21273/hortsci15997-21
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen, Calcium, and Magnesium Inconsistently Affect Tree Growth, Fruit Yield, and Juice Quality of Huanglongbing-affected Orange Trees

Abstract: The bacterial disease Huanglongbing (HLB) has drastically reduced citrus production in Florida. Nutrients play an important role in plant defense mechanisms and new approaches to manage the disease with balanced nutrition are emerging. Nutrients like nitrogen (N), calcium (Ca), and magnesium (Mg) could extend the productive life of affected trees, although interactions among these nutrients in HLB-affected citrus trees are still unclear. A 2-year study was established in Florida to determine the response of HL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Percent change in yield was calculated using the method described by Esteves et al. (2021) in Equation (). Canopy efficiency that measures the ratio of yield per canopy volume was calculated by dividing fruit yield per plot by canopy volume for the plot as described in the following equation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Percent change in yield was calculated using the method described by Esteves et al. (2021) in Equation (). Canopy efficiency that measures the ratio of yield per canopy volume was calculated by dividing fruit yield per plot by canopy volume for the plot as described in the following equation.…”
Section: Methodsmentioning
confidence: 99%
“…Fruits were then used for juice quality (including soluble solids-Brix, titratable acid, and Brix/acid ratio). Percent change in yield was calculated using the method described by Esteves et al (2021) in Equation ( 5). Canopy efficiency that…”
Section: Yield Fruit Quality Measurements and Canopy Efficiencymentioning
confidence: 99%
“…There has been multiple research that supports the use of ENPs to mitigate the damaging effects of HLB [ 18 , 22 , 24 , 39 , 40 , 41 , 42 ]. When citrus trees are infected by HLB disease, they show signs of micronutrient deficiencies (for example zinc, manganese, and iron) and this may be because the severity of HLB causes phloem plugging, thus limiting nutrient translocation within the plant [ 14 , 25 ] and as a result damages more than 40% of the fibrous roots [ 7 , 32 ], which may, in turn, inhibit nutrient absorption.…”
Section: Efforts To Mitigate the Effects Of Hlbmentioning
confidence: 99%
“…From the information gathered, it appears that the HLB-affected trees require more micronutrients than what is traditionally recommended for citrus production in Florida to achieve optimum nutrition. It has also been observed that foliar application of micronutrients to supplement soil-applied nutrients is able to correct deficiencies for HLB-affected trees [ 22 , 24 , 39 , 42 ]. HLB can impact yield due to poor growth and development, because of reduced root biomass and nutritional deficiencies [ 6 , 7 , 8 , 19 ], it is important that growers supply optimum nutrition while the tree is still young (between 1–4 years old).…”
Section: What Is Knownmentioning
confidence: 99%
“…Many researchers have begun to investigate magnesium nutrition and the determination of magnesium requirements for economically important crops [23] such as 'Washington navel' orange trees [24] and banana plants, and they have reported on the influence of magnesium on yield and fruit quality, stating that magnesium fertilization increased the yield and fruit quality of the aforementioned fruit species [25]. In addition, using the magnesium application can induce a state of magnesium deficiency during growing [26].…”
Section: Introductionmentioning
confidence: 99%